Incidence of venous thromboembolism following the neoadjuvant chemotherapy regimen for epithelial type of ovarian cancer. Issue 42 (October 2017) - Chavan, Devendra Manik; Huang, Zhen; Song, Kun; Parimi, Leela Rani Haricharan; Yang, Xing Sheng; Zhang, Xiangning; Liu, Peishu; Jiang, Jie; Zhang, Youzhong; Kong, Beihua; Li, Li
Abstract : Abstract: This study aims to analyze the risk of venous thromboembolism (VTE) in patients receiving neoadjuvant chemotherapy (NACT) for epithelial ovarian cancer (EOC). A retrospective audit was conducted examining 147 patients treated for EOC. Surgical treatment with curative intent, with or without NACT and adjuvant chemotherapy, is the treatment approach, which was modified according to the patient's condition. The incidence of VTE with the most commonly used chemotherapy regimen, carboplatin, cisplatin, paclitaxel, docetaxel, and others were evaluated. This study found a 13.6% incidence of VTE in patients undergoing therapy with curative intent for EOC. No association was seen between NACT and VTE compared to VTE after standard treatment: 2/16 (12.5%) vs 5/131 (3.8%) ( P = .16). Univariate and multivariate analyses also demonstrated that NACT has no risk for VTE with odds ratio (OR) = 0.89 (95% CI = 0.18–4.28) and P = 1. Results did not vary significantly with the type of chemotherapy used. Furthermore, increased incidence of VTE as an incidental finding supports the well-established role of malignancy in VTE occurrence. Univariate and multivariate analyses demonstrated that VTE occurred more frequently in menopausal women than nonmenopausal women (17.9% vs 5.8%) with OR = 3.55 (95% CI = 0.99–12.78) and P = .04 in patients aged ≥60 (19.3% vs 10%) with OR = 2.15 (95% CI = 0.83–5.57) and P = .13 but is not statistically significant. We conclude that NACT has no association with VTE and the currently used common chemotherapeutic drug combinations for ovarian cancer carry the minimal risk of thromboembolic events.